Inthe home...and Norberto at bat - Juan A. Martínez de Osaba y Goenaga (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2013)
Sport is, like so many areas of life, and literary source accordingly. Comment on a book by Norberto Codina, Venezuela birth, Cuban citizen of the world and by conviction, is no easy task. And can not the chronicler but admire the difficult conjunction derived from one linked to baseball poetic soul, which split into inherited knowledge acquired and promoted in the daily work.